ANALISIS PENGUKURAN GAYA KEPEMIMPINAN (Studi kasus pada Perusahaan Kerajinan Palupi Craft) - Insani, Akbar; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2015)
The aim of this research is to investigate the leadership style applied in Palupi Craft â€“ a handicraft company specializing in batik bag and leather goods. Despite the continuous growth in company sales, the company owner was not able to describe the leadership style she implements in the company. To measure and determine the leadership style used in Palupi Craft, this study utilize Leadership Questionnaire developed by Bass and Avolio. The questionnaires were distributed to all Palupi Craft employees, and the results were described using descriptive technique.Â  This study reveals that the Palupi Craft owner tend to utilize transactional leadership style in managing her business. Discussion and recommendation for future research was also included.